Blood pressure control and clinical outcomes in acute intracerebral haemorrhage: a preplanned pooled analysis of individual participant data. Issue 9 (September 2019) - Moullaali, Tom J; Wang, Xia; Martin, Reneé H; Shipes, Virginia B; Robinson, Thompson G; Chalmers, John; Suarez, Jose I; Qureshi, Adnan I; Palesch, Yuko Y; Anderson, Craig S
Summary: Background: Uncertainty persists over the effects of blood pressure lowering in acute intracerebral haemorrhage. We aimed to combine individual patient-level data from the two largest randomised controlled trials of blood pressure lowering strategies in patients with acute intracerebral haemorrhage to determine the strength of associations between key measures of systolic blood pressure control and safety and efficacy outcomes. Methods: We did a preplanned pooled analysis of individual patient-level data acquired from the main phase of the Intensive Blood Pressure Reduction in Acute Cerebral Haemorrhage Trial (INTERACT2) and the second Antihypertensive Treatment of Acute Cerebral Hemorrhage (ATACH-II) trial. These trials included adult patients aged 19–99 years with spontaneous (non-traumatic) intracerebral haemorrhage and elevated systolic blood pressure, without a clear indication or contraindication to treatment. Patients were excluded if they had a structural cerebral cause for the intracerebral haemorrhage, had a low score (3–5) on the Glasgow Coma Scale, or required immediate neurosurgery. Our primary analysis assessed the independent associations between three post-randomisation systolic blood pressure summary measures—magnitude of reduction in 1 h, mean achieved systolic blood pressure, and variability in systolic blood pressure between 1 h and 24 h—and the primary outcome of functional status, as defined by the distribution of scores on the modified Rankin Scale at 90 days post-randomisation. We analysed the systolic blood pressure measures as continuous variables using generalised linear mixed models, adjusted for baseline covariables and trial. The primary and safety analyses were done in a modified intention-to-treat population, which only included patients with sufficient data on systolic blood pressure. Findings: 3829 patients (mean age 63·1 years [SD 12·9], 1429 [37%] women, and 2490 [65%] Asian ethnicity) were randomly assigned in INTERACT2 and ATACH-II, with a median neurological impairment defined by scores on the National Institutes of Health Stroke Scale of 11 (IQR 6–16) and median time from the onset of symptoms of intracerebral haemorrhage to randomisation of 3·6 h (2·7–4·4). We excluded 20 patients with insufficient or no systolic blood pressure data, and we imputed missing systolic blood pressure data in 23 (1%) of the remaining 3809 patients. Overall, the mean magnitude of early systolic blood pressure reduction was 29 mm Hg (SD 22), and subsequent mean systolic blood pressure achieved was 147 mm Hg (15) and variability in systolic blood pressure was 14 mm Hg (8). Achieved systolic blood pressure was continuously associated with functional status (improvement per 10 mm Hg increase adjusted odds ratio [OR] 0·90 [95% CI 0·87–0·94], p<0·0001). Symptomatic hypotension occurred in 28 (1%) patients, renal serious adverse events occurred in 26 (1%) patients, and cardiac serious adverse events occurred in 99 (3%) patients. Interpretation: Our pooled analyses indicate that achieving early and stable systolic blood pressure seems to be safe and associated with favourable outcomes in patients with acute intracerebral haemorrhage of predominantly mild-to-moderate severity. Funding: None.